A REVIEW ON: REMOVAL OF LEAD FROM WASTE WATER BY VARIOUS TECHNIQUES AND METHODS (International Association of Biologicals and Computational Digest, 2022)
Lead is one of the most dangerous compounds present on earth. The presence of this particular compound in waste water causes toxicity to environment and also to human beings. Various methods has been analysis on different ways to carry out the lead content from water like the use of activated charcoal, some natural and synthetic adsorbents, extraction from waste water ,ion exchange, various precipitation techniques has been analysed for removal of lead. There are few models like Langmuir and frend lich isotherm are used in these methods for removal of lead. The removal of lead is found to be a sum of adsorption induced by ion exchange and precipitation of lead hydroxide. The main sources of the lead are these heavy industries, smoke from transportation both by natural and manmade activities are responsible. The various parameters that affect these methods are the pH concentration, time contact and metal ion concentration, and also its adsorption capacity. This review article presents the information about the removal of lead (Pb) and (Pb+2) ions from various techniques and models from waste water.
Keywords: Waste Water, Lead, Techniques, biosorbents